Effects of personal relative deprivation on the relationship between anger rumination and aggression during and after the COVID‐19 pandemic lockdown: A longitudinal moderated network approach. Issue 3 (13th January 2023) - Tao, Yanqiang; Niu, Haiqun; Li, Yue; Liu, Xueting; Wang, Shujian; Ma, Zijuan; Hou, Wenxin; Liu, Xiangping
Abstract: Introduction: Several studies have demonstrated a directional link between rage rumination and aggression. However, recent research suggests that this relationship is bidirectional. The current study examined the complex relationships between anger rumination and aggression using a moderated network approach in a longitudinal design while considering personal relative deprivation. Method: A total of 665 participants (59.25% female, agemean±SD  = 19.01 ± 1.25) were enrolled at two‐time points. Assessments included self‐report measures of the Anger Rumination Scale, Buss‐Perry Aggression Questionnaire, and Relative Deprivation Scale. A Moderated Network Model (MMN) was used to test the complex links among anger rumination, aggression, and personal relative deprivation. Results: The analysis revealed that the link between anger rumination and aggression was complex and bidirectional. Notably, as the level of personal relative deprivation increased, verbal aggression had a positive conditional effect on anger afterthoughts in Wave 2, and thoughts of revenge had a positive conditional effect on verbal aggression in Wave 2. Moreover, as the first discovery, anger afterthoughts and anger had a negative conditional effect on each other across levels of personal relative deprivation in Wave 2. In addition, network comparison indicates that the MNMs structure was significantly different across timepoints, implying that anger rumination and aggression were inextricably linked in college students during isolation and that this complicated relationship was weakened after isolation. Conclusions: This study deepens our understanding of the bidirectional relationships between anger rumination and aggression and recognizes the moderating role of personal relative deprivation.